“WHEN ENGLISH RINGS THE BELL”: An English Textbook Analysis - Rias Wita Suryani (English Language Teaching and Research, 2018)
Textbook analysis has become a crucial need, it is important to help teacher to be more selective in choosing suitable textbook for students. This article intends to describe whether the English textbook “When English Rings the Bell” published by Ministry of Education and Culture of Indonesia met the criteria of textbook evaluation. It considered four criteria, objective, language skills, content, and design. The criteria were developed based on the adaptation of material evaluation criteria proposed by Cunningsworth, Byrd, and BSNP. The design of this research was descriptive qualitative research. The collection of the data was done through evaluation checklist and rating scale. Findings show that the textbook toward the four criteria of consideration reached 74%. It means that the textbook was categorized as good. It can be used in the teaching and learning process but it needed a lot of improvements.Key words: English textbook, textbook evaluation criteria